2008
DOI: 10.1179/146532808x270644
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of unnecessary transfusion and intravenous fluids in severely malnourished children is not enough to reduce mortality

Abstract: Aim: To test whether standardising the use of blood transfusions and intravenous (IV) infusions could reduce fatality in severely malnourished children admitted to Mulago Hospital, Kampala. Methods: Improved adherence to the WHO protocol for blood transfusion and IV fluids was effected in patients with severe malnutrition by continuous medical education. A 'before and after' design was used to study 450 severely malnourished children (weight-for-height ,23 Z-score or presence of oedema) under 60 months of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Although, the WHO guidelines for the management of SAM represent a major advancement in reduction of SAM‐related deaths in LMICs, the guideline implementation varies within and between countries causes large variation of CFR . This study found that, majority of the facilities in Asia had adequate resources to manage SAM in comparison to Africa and Latin America, where most of the facilities lacked adequately trained human resource, lack of supplies, inadequate space and resources and faulty case‐management . Despite of having better equipped facilities, Bangladeshi children admitted with acute severe complications died within 2 days whereas children from Africa with chronic condition survived up to 4 weeks .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although, the WHO guidelines for the management of SAM represent a major advancement in reduction of SAM‐related deaths in LMICs, the guideline implementation varies within and between countries causes large variation of CFR . This study found that, majority of the facilities in Asia had adequate resources to manage SAM in comparison to Africa and Latin America, where most of the facilities lacked adequately trained human resource, lack of supplies, inadequate space and resources and faulty case‐management . Despite of having better equipped facilities, Bangladeshi children admitted with acute severe complications died within 2 days whereas children from Africa with chronic condition survived up to 4 weeks .…”
Section: Discussionmentioning
confidence: 86%
“…17 This study found that, majority of the facilities in Asia had adequate resources to manage SAM 14,18 in comparison to Africa and Latin America, where most of the facilities lacked adequately trained human resource, lack of supplies, inadequate space and resources and faulty case-management. 5,13,15,16,[19][20][21] Despite of having better equipped facilities, Bangladeshi children admitted with acute severe complications died within 2 days 14,18 whereas children from Africa with chronic condition survived up to 4 weeks. 13 Thus, the severity of illness and presence of different co-morbid condition might have played crucial role behind high CFR in SAM children.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of recent studies, we found one before/after study [25], two retrospective chart reviews [26,27], one quasi-experimental study [28] and four prospective cohorts [29-33] that examined the case fatality rates and recovery rates of children with SAM treated according to the WHO protocol or an adapted WHO protocol. There was also one cluster RCT that compared inpatient treatment to home-care and day-care treatment [34,35]; this study contained methodological issues and did not adequately describe the intervention (see additional file 3 for study assessment).…”
Section: Resultsmentioning
confidence: 99%
“…32 However, a subsequent study of 450 severely malnourished children with appropriate use of transfusions and infusions failed to reduce the case fatality rate which remained at 24.8%. 33 Despite the unchanged overall mortality, the change to appropriate blood transfusions and IV infusions did improve outcomes.…”
Section: Risk Factors For Mortalitymentioning
confidence: 99%